Assessing farmer’s perceptions of Sunda leopard cats (Prionailurus javanensis) in rice fields area of West Sumatra, Indonesia - AHMAD FAKHRI; RIZALDI RIZALDI; AADREAN AADREAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fakhri A, Rizaldi, Aadrean. 2024. Assessing farmer’s perceptions of Sunda leopard cats (Prionailurus javanensis) in rice fields area of West Sumatra, Indonesia. Biodiversitas 25: 4397-4405. Land use change in agricultural areas has caused wildlife to adapt to living in these areas, such as rice fields. Sunda leopard cats (Prionailurus javanensis) in rice fields have rice field rats as their main prey, which are pests. This cat is useful as a biocontrol of rat pests, but human activities threaten its presence. This study aims to determine farmers' perceptions of the importance of Sunda leopard cat’s presence, its conservation and protection, and farmer participation in its conservation in rice fields of Nagari Batu Taba, Agam Regency, West Sumatra. In June 2023, we employed purposive sampling and conducted semi-structured interviews involving 27 farmers. A mixed-methods approach was used to analyze the data. The results of this study showed that farmers' perceptions were in the 'Good' category for the importance of the cat's presence (76.74%), for conservation and protection (78.08%), and for farmer participation in conservation efforts (93%) in rice fields of Nagari Batu Taba. Farmers recognize the important role of these cats in the rice field ecosystem as a biological pest control of rice field rats. However, human activities in human-dominated landscapes pose a threat to the survival of these cats. Coexisting in the same area has motivated farmers to undertake conservation efforts to protect cat presence in the rice fields. Therefore, effective conservation efforts involving farmers, researchers, government agencies, and non-governmental organizations are essential. However, the need for further research to develop conservation strategies and evaluate the conservation status of Sunda leopard cat is urgent and cannot be overstated.